"Africa is the future": trajectories of ‘repats’ entrepreneurs in Senegal's cultural sectors - (:unkn) unknown (My University, 2024)
Situated at the crossroads of sociology of migration and sociology of culture and cultural practices, this thesis aims to examine how ‘repats’ settle in Senegal through the prism of their entrepreneurial activities in cultural sectors. This research, based on a fieldwork carried out in Dakar, Senegal, from 2019 to 2023, sheds light on the category of ‘repats’ : highly qualified populations from the African diasporas who spontaneously resettle in Africa without the aid of return programmes. These circulating elites are both heirs and supporters of international capital and experience and position themselves as cultural intermediaries of globalisation in Senegal. These men and women, aged between 30 and 40, want to assert their youth, often associated with values of dynamism and innovation. They want to embody a new generation of enterprising children of the continent. They take advantage of social networks to create digital content to promote Africa’s wealth and opportunities. The term ‘repat’ conveys the idea of return and homeland, and is constructed in opposition to that of ‘expat’. This mediatic category emerges in a particular post-colonial context driven by Afro-optimistic discourses and marked by the reconfiguration of socio-economic partnerships in Africa. The visibility of repats on digital social networks fuels a market for returning to Africa that is being built up in Senegal and targets the African diasporas. By linking their migratory dynamics to their digital practices, the repats contribute to the transformation of Senegal's cultural sectors and create unique forms  of territorial anchorage.
Keywords: African Research